2008
DOI: 10.1210/me.2007-0515
|View full text |Cite
|
Sign up to set email alerts
|

Welcoming β-Catenin to the Gonadotropin-Releasing Hormone Transcriptional Network in Gonadotropes

Abstract: GnRH binds its G-coupled protein receptor, GnRHR, on pituitary gonadotropes and stimulates transcription of Cga, Lhb, and Fshb. These three genes encode two heterodimeric glycoprotein hormones, LH and FSH, that act as gonadotropins by regulating gametogenesis and steroidogenesis in both the testes and ovary. GnRH also regulates transcription of Gnrhr. Thus, regulated expression of Cga, Lhb, Fshb, and Gnrhr provides a genomic signature unique to functional gonadotropes. Steadily increasing evidence now indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…implicated (Surendran & Simon 2003). We have not examined the role of Wnt signalling in regulating CNP expression in the pituitary, yet recent observations of GNRH-dependent b-catenin signalling in gonadotrophs (Salisbury et al 2008) suggest this pathway could be an alternative regulator of Nppc transcription in the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…implicated (Surendran & Simon 2003). We have not examined the role of Wnt signalling in regulating CNP expression in the pituitary, yet recent observations of GNRH-dependent b-catenin signalling in gonadotrophs (Salisbury et al 2008) suggest this pathway could be an alternative regulator of Nppc transcription in the pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent data have established a major role for the Wnt/ b-catenin signaling pathway in regulating pituitary development and growth (21). These studies demonstrated that b-catenin plays an essential role in transducing the GnRH signal by interacting with multiple DNA-binding proteins in gonadotropes (22)(23)(24). In addition, in a mouse model, b-catenin acts as a cofactor for a number of pituitary transcription factors that control pituitary cell specification and exert both stimulatory (prop1 in regulating expression of pit-1) and inhibitory (Hesx1) effects (21,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Further, b-catenin appears as an essential cofactor of SF1, enhancing its synergistic effects with GnRH to stimulate the transcription of LHB/Lhb genes through GnRH-mediated changes in EGR1; thus, optimal LH levels are synthesised to ensure sustained pulsatile secretion (Fig. 2) [51,52]. Over-expression of axin (which after binding to b-catenin initiates its degradation) interferes with the activity of the LHB promoter [52].…”
Section: The Involvement Of B-catenin In the Regulation Of Hormonal Gmentioning
confidence: 99%
“…1 b- and its down-regulation with T3 (triiodo-thyronine) treatment for 6 h; the nuclear b-catenin protein and functional b-catenin/TCF response promoter were significantly reduced with T3 treatment, such changes resulting in growth arrest of thyrotroph tumors in vitro [54]. [51]. Interactions between EGR1, SF1, Pitx1 and b-catenin determine the GnRH response mediating LHB/Lhb gene transcription.…”
Section: The Involvement Of B-catenin In the Regulation Of Hormonal Gmentioning
confidence: 99%